Krátkodobé výsledky náhrady kořenového kloubu palce ruky Ivory® - Závodský, I; Pavličný, R; Holinka, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
PURPOSE OF THE STUDY Trapeziometacarpal osteoarthritis affects primarily postmenopausal middle-aged and older women. Total joint replacement is one of the surgical treatment options for symptomatic advanced degenerative changes of the carpometacarpal joint. This study aims to evaluate the short-term functional and radiological results of the Ivory ® prosthesis with the minimum followup period of three years after the surgery. MATERIAL AND METHODS Presented are the results of 48 total trapeziometacarpal joint replacements in the group of 40 patients composed of 36 women and 4 men. The age of patients ranges from 41 to 75 years (median 56 years), with the ratio between the dominant and non-dominant upper extremity 23:25. The follow-up period ranged from 36 to 63 months (median 52 months). The surgery was indicated in patients with symptomatic trapeziometacarpal arthrosis of stage II, III and early stage IV according to Eaton-Glickel once the conservative therapy had failed. In all the patients, the evaluation of the function and pain of the operated joint by DASH score, the range of motion -thumb opposition by Kapandji score were carried out at regular intervals pre- and postoperatively, the radiological evaluation of the stage of degenerative joint condition was done preoperatively, whereas the position of the implant and the lengthening of the first column of the finger were assessed postoperatively. RESULTS Subjectively, the patients were satisfied with the result of the surgery. After the joint replacement, in 65% of cases the patients reported full satisfaction with no difficulties present, in 31% of cases the patients suffered from pain during loading, in 4% of cases the patients reported also occasional pain at rest. Postoperatively, the total DASH score values decreased from the mean preoperative value of 52.79 to 10.4 points at a three-year follow-up. The average value of pain dropped from 3.46 to 1.44 points 3 years after the surgery. The average range of motion - thumb opposition by Kapandji score increased from 8.57/10 to 9.85/10 one year after the surgery. The difference between the values of average increase in length of the first column of the finger was 0.14 mm in favour of the sub-group of symptomatic cases. In the evaluated group, the need for revision was determined in 4 implants. In 1case for aseptic loosening of the cup and three times for dislocation. After 36 months, 47 of 48 implants were in situ, the overall three-year survival was achieved in 97.9%. The most frequent postoperative complication was the occurrence of De Quervain s tenosynovitis (10%). DISCUSSION Currently, most of the newer types of modular uncemented hydroxyapatite-coated total "ball and socket" joint replacements present acceptable medium-term, and in some cases even long-term, results regarding the survival. The most pressing issue continues to be the survival of implants, particularly the failure of the trapezial component and the associated risk of revision surgery. Good postoperative results can be achieved by accurate indication, carefully applied cup implant and good postoperative cooperation of patients. The complementary study did not confirm that the lengthening of the thumb causes the postoperative development of De Quervain s tenosynovitis. CONCLUSIONS The uncemented first carpometacarpal joint total replacement using the Ivory ® prosthesis brings about very good shortterm functional and radiological results, with no occurrence of early aseptic loosening of the implant. Key words:rhizarthrosis, arthroplasty, carpometacarpal joint prosthesis, uncemented.
Keywords: spokojenost pacientů; dospělí; Carpometacarpal Joints; osteoartróza; radiografie; Radiography; Adult; Arthroplasty, Replacement; výsledek terapie; Patient Satisfaction; karpometakarpální klouby; artroplastiky kloubů; lidé; pooperační komplikace; Treatment Outcome; následné studie; Follow-Up Studies; Postoperative Complications; Trapezium Bone; Aged; Osteoarthritis; Joint Prosthesis; protézy kloubů; lidé středního věku; senioři; trapézová kost; Middle Aged; Humans